Notice of a Greek Medical Inscription found at Chester (Proceedings of the Society of Antiquaries of Scotland, 1856)
The author comments on the recent discovery of a rare Greek inscription in the British Isles. He suggests that the tablet may have been part of an altar to Aesculapius and Hygenia raised by a Greek physician working for the Emperor Hadrian in the second century.